(3Mb GdeQCI aj GdeSGhGI HGdQLd Hjf GdbGfhf GdOhdj hGdTQjYI GdESdGejI (B: s (3OQGSI ebGQfI aj EWGQ GdNUhUjI GdKbGajI ddOhd GdESdGejI (B/ s - (3YjGO Ydi TYHGf OQHGds; (3CMeO CHhGdhaG eMeOs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2017)
(3CNab efgLG YGdejI Mbhb GdEfSGf hfSHjJgG aj YdGL GdJYGQV Hjf Mb GdeQCI aj GdeSGhGI HGdQLd hbhGfjf GdCSQI aj eUQ hdjHjG hGdJj JYGed GdeQCI eYGedI eNJdaI Yf GdQLd aj eSGFd JYOO GdRhLGJ hGdWdGb hGdejQGK(B. (3hdgPG bOeJ GdOQGSI efgLkG HOjdkG jYGdL gPG GdJYGQV HWQjbI bGfhfjI(B: (3hjJeKd aj eHOCj GdJfGSH hGdgGeT GdJbOjQj(B. (3WHbJ GdOQGSI gPjf GdeHOCjf aGfJgJ Edi Cf JONd GdOhdI aj eUQ hdjHjG aj Mb GdeQCI aj GdeSGhGI HGdQLd aj TDhf JYOO GdRhLGJ hGdWdGb hGdejQGK gh JONd VQhQj dJdHjI MGLI GLJeGYjI edMI Jahb GdMGLI Edi EYeGd Mb GdeQCI aj GdeSGhGI HGdQLd aj gPg GdeSGFd(B. (3ceG CKHJJ JMbb MGdI GdJfGSH aj GdELQGAGJ GdJbjjOjI ef MjK Ef hSGFd GdJbjjO GdeJHfGI aj bhGfjf GdOhdJjf gj CNa GdhSGFd MOkI dJMbjb GdCgOGa GdeTQhYI GdeJZjGI ef GdJbjjO(B. (3hHGdJGdj(B: (3aEf GdbjhO GdeaQhVI Ydi Mb GdeQCI aj GdeSGhGI aj GdTDhf GdePchQI ehGabI ddTQhW GdebQQI aj GdbGfhf GdOhdj dMbhb GdEfSGf(B. s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdOhdi, (B2017s
(3HHdjhLQGajG(B: (3UaMGJ (B633-673s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdOhdjs; (3GdMb ai GdNUhUjI GdKbGajI s; (3GdMb aj GdeSGhGI Hjf GdLfSjfs; (3GdeSGhGI GdYGOdIs; (3Mbhb GdeQCI ai GdGSdGe s; (3fXQjI YGdejI Mbhb GdGfSGfs; (3eHOG GdJfGSHs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdOhdjs